2012
DOI: 10.4103/0378-6323.100583
|View full text |Cite
|
Sign up to set email alerts
|

Peeling skin syndrome in eight cases of four different families from India and Bangladesh

Abstract: Peeling skin syndrome (PSS) is a rare recessively inherited ichthyosiform genodermatoses characterized by superficial skin peeling. This has 2 subtypes, acral (APSS; OMIM 609796) and generalized form (OMIM 270300). The later has been subdivided into type A (non-inflammatory) and type B (inflammatory). Eight cases of peeling skin syndrome in 4 families were recorded over a period of 5 years. They were diagnosed clinically and confirmed histopathologically. Disease onset ranged from birth to childhood age (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
4
1
1
Order By: Relevance
“…reported a case series of 8 patients from India and Bangladesh with early onset of SPS and age at presentation being 7–35 years. [ 1 ] In contrast to the above studies, our patient reported at the age of 42 years with the onset of skin peeling at the age of 41 years, which is a late onset type of SPS. Although various studies have reported a family history of SPS, there was no family history of SPS in our patient.…”
contrasting
confidence: 68%
See 2 more Smart Citations
“…reported a case series of 8 patients from India and Bangladesh with early onset of SPS and age at presentation being 7–35 years. [ 1 ] In contrast to the above studies, our patient reported at the age of 42 years with the onset of skin peeling at the age of 41 years, which is a late onset type of SPS. Although various studies have reported a family history of SPS, there was no family history of SPS in our patient.…”
contrasting
confidence: 68%
“…It is characterized by painless superficial peeling of the skin with or without vesiculation. [ 1 2 ] Apart from the skin shedding, the affected individuals are usually otherwise well. No effective treatment has been found so far for this condition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic drugs include corticosteroids at low doses of 1-2 mg prednisone per kg per day for 4-6 weeks with evaluation of response and tapering of dose to prevent HPA axis suppression, growth retardation, cushingoid features, bony defects, abnormal carbohydrate and fat metabolism. Sarma N et al 8 reported that retinoid being unsuccessful in treating PSS.…”
Section: Discussionmentioning
confidence: 99%
“…Występują objawy zapalenia spojówek, warg i głębokie pęknięcia typu perléche oraz świąd. W tej odmianie brakuje badań molekularno-genetycznych [24][25][26].…”
Section: Omówienieunclassified